Physicochemical Properties of Wild Yam (Dioscorea villosa) Starch - Abraham Olasupo Oladebeye; Aderonke Adenike Oladebeye; Jacob Olalekan Arawande (International Journal of Food Science)
Native starch extracted from wild yam (Dioscorea villosa) was evaluated for its intrinsic physicochemical properties. From the results, essential metals such as K, Ca, P, and Fe were detected along with some nonessential heavy metals below the WHO permissible limits. Bulk density was 0.13–0.63 g/mL. The water absorption capacity, oil absorption capacity, swelling power, and solubility of the starch were pH-responsive. Thermal profiles showed onset temperature, To (59.21 °C), peak temperature, Tp (60.22 °C), endset temperature, Tc (63.12 °C), gelatinization enthalpy, ΔHgel (0.54 J/g), temperature range of gelatinization, R (3.91 °C), and peak height index, PHI (1.87 J/g °C). Exhibiting a crystallite size of 0.03 nm, absorption peaks of 15.3119°, 24.4120°, and 18.4170°, corresponding to interplanar d-spacings of 3.7500 Ǻ, 5.14000 Ǻ, and 4.954610 Ǻ, were obtained. Evidence of C–H at 1338.1 cm-1, C–O at 640.0 cm-1, C–H stretch at 2829.7 cm-1, and a strong and broad O–H group at 3291.2 cm-1 were obtained. The starch granules had low particle sizes, were homogeneous, and were aggregates of irregular shapes. At a lower pH (2-4), the wild yam starch studied could be a potential absorbent material in the production of disposable diapers and female napkins and as biodegradable films due to its high hydrophobicity at a high pH (8-12).